Downregulation of SLC44A4 in nasopharyngeal carcinoma is associated with malignant progression, B-cell/TLS-related immune features, and sensitivity to DNA-damaging agents - Qian Liu; Yiyue Yin; Guangxian Hu; Hongde Li; Min Li; Xiangjian Luo; Wenbin Liu (PLoS ONE, 2026)
Nasopharyngeal carcinoma (NPC) is characterized by aggressive progression, frequent metastasis, and heterogeneous therapeutic responses. Through integrated bulk transcriptomic datasets, single-cell analysis, clinical specimens, and NPC cell lines, we identified SLC44A4, a member of the choline transporter-like family, as a significantly downregulated gene in NPC. Transcriptomic analyses revealed that SLC44A4 expression was negatively associated with oxidative phosphorylation–related genes, DNA damage repair pathways, and malignant transcriptional programs related to proliferation, invasion, and metastasis. Moreover, SLC44A4-high tumors exhibited increased B-cell infiltration and enrichment of TLS-related transcriptional signatures. In vitro, SLC44A4 overexpression in NPC cells suppressed proliferation, colony formation, migration, and invasion, induced G0/G1 cell-cycle arrest, reduced expression of oxidative phosphorylation–related proteins, and selectively upregulated CXCL10. SLC44A4 overexpression also increased sensitivity to DNA-damaging agents, including temozolomide, doxorubicin, cisplatin, olaparib, and etoposide, while decreasing sensitivity to 5-fluorouracil. Together, these findings identify SLC44A4 as a potential tumor-suppressive factor in NPC and suggest that SLC44A4 may serve as a biomarker for metabolic state, B-cell/TLS-associated immune features, and vulnerability to DNA damage–based therapies.